The bondage breaker - Anderson, Neil T., 1942- (Eugene, OR. : Harvest House Publishers, 2000)
"'The bondage breaker' reveals the whys and hows of spiritural warfare and exposes Satan's battle for your mind. 'The bondage breaker' shares the powerful truth that will break even the most stubborn habits or private sins. Learn the truth of who you are in Christ and what it means to be a child of God. Knowing your spiritual identity and position in Christ is the essential truth that will set you free" --Cover, p. 4.
You don't have to live in the shadows -- Finding your way in the world -- You have every right to be free -- You can win the battle for your mind -- Confronting the rebel prince -- Jesus has you covered -- Manipulating spirits -- The lure of knowledge and power -- Tempted to do it your way -- Accused by the father of lies -- The danger of deception -- The danger of losing control -- Steps to freedom in Christ -- Helping others find freedom in Christ.
Includes bibliographical references (p. 285-286) and index.
Keywords: Spiritual warfare; Spiritual warfare